2022
DOI: 10.3390/jcm11040991
|View full text |Cite
|
Sign up to set email alerts
|

Music Intervention for Pain Control in the Pediatric Population: A Systematic Review and Meta-Analysis

Abstract: Music intervention (MI) has been applied as an effective adjunctive treatment for pain control in various clinical settings. However, no meta-analysis has yet been published on the analgesic effects of MI in infants and children. We performed a systematic review of PubMed, EMBASE, Web of Science, and Cochrane Library databases to identify randomized controlled trials (RCTs) with the keywords “pain” AND “music therapy” from inception to January 2022. Primary outcomes were pain intensity and vital signs. Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 83 publications
0
11
0
2
Order By: Relevance
“…Music therapy is a promising non-medical intervention to reduce stress and pain in preterm and sick newborn infants and children [ 1 , 2 , 3 , 4 ]. Preterm infants are repetitively exposed to stressful and painful stimuli during their initial hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Music therapy is a promising non-medical intervention to reduce stress and pain in preterm and sick newborn infants and children [ 1 , 2 , 3 , 4 ]. Preterm infants are repetitively exposed to stressful and painful stimuli during their initial hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence on new treatments (e.g., esketamine nasal spray, repetitive transcranial magnetic stimulation, psilocybin) may not be available in every country [ 20 ]. Studies are still needed to assess the benefits of the cognitive behavioral approach [ 21 ] or complementary therapy (e.g., music, mindfulness) [ 22 ] for patients with co-occurring physical and psychological symptoms, such as inflammation or long COVID.…”
Section: Common Pathomechanisms Of Somatic and Psychiatric Comorbiditymentioning
confidence: 99%
“…Subsequently, both the study carried out by the European EURORDIS Alliance in 2003–2008 on 12,000 patients [ 4 ] and the ENSERio study conducted in Spain in 2016–2017 [ 1 ], as well as research undertaken in other countries [ 5 ], confirmed that these problems still exist; in particular, almost half of the patients continue to experience a delay in diagnosis and lack adequate treatment. In fact, one of the goals set by the International Rare Diseases Research Consortium (IRDiRC) for the period 2017–2027 is the confirmation of diagnosis in less than one year [ 6 ].…”
Section: Introductionmentioning
confidence: 99%